(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2023)
In this research, humidity sensors based on Polyvinyl Alcohol (PVA)-Tin Oxide (SnO2) have been designed and fabricated using screen printing. The sensor devices were fabricated on Alumina Substrate (Al2O3) with Silver (Ag) as the electrode material. The number of fingers on the electrodes was varied to obtain different sensor resistance values. SnO2 was added to the PVA sensing layer with variations in the composition. The size of granules formed from mixing PVA-SnO2 material will also be observed.